2020
DOI: 10.1038/s41416-019-0720-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating DNA methylation measures to improve clinical risk assessment: are we there yet? The case of BRCA1 methylation marks to improve clinical risk assessment of breast cancer

Abstract: Current risk prediction models estimate the probability of developing breast cancer over a defined period based on information such as family history, non-genetic breast cancer risk factors, genetic information from high and moderate risk breast cancer susceptibility genes and, over the past several years, polygenic risk scores (PRS) from more than 300 common variants. The inclusion of additional data such as PRS improves risk stratification, but it is anticipated that the inclusion of epigenetic marks could f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Involvement of epigenetic alterations in the development of various diseases have been previously demonstrated and is being confirmed in increasingly larger-scale epigenetic studies ( Wong et al , 2020 ). It is also predicted that epigenetic alterations in a higher than currently anticipated number of cancer-predisposing genes might affect cancer risk ( Widschwendter et al , 2018 ).…”
Section: Resultsmentioning
confidence: 67%
“…Involvement of epigenetic alterations in the development of various diseases have been previously demonstrated and is being confirmed in increasingly larger-scale epigenetic studies ( Wong et al , 2020 ). It is also predicted that epigenetic alterations in a higher than currently anticipated number of cancer-predisposing genes might affect cancer risk ( Widschwendter et al , 2018 ).…”
Section: Resultsmentioning
confidence: 67%
“…Involvement of epigenetic alterations in the development of various diseases have been previously demonstrated and is being confirmed in increasingly larger-scale epigenetic studies (Wong et al, 2020). It is also predicted that epigenetic alterations in a higher than currently anticipated number of cancerpredisposing genes might affect cancer risk (Widschwendter et al, 2018).…”
Section: Resultsmentioning
confidence: 78%
“…A recent comparison of several of the most commonly used clinical models (i.e., Gail, BRCAPRO, BCSC, Claus, IBIS) in a large, predominantly White US screening population indicated that the models were generally well-calibrated (O/E range: 0.78-0.97) but with only moderate discrimination (AUC range: 0.61-0.64) [304]. Expansion of these models to include multiple biomarkers (e.g., mammographic density and/or other imaging features, polygenic risk scores, endogenous hormones, epigenetics, metabolomics), and the development and validation of models across race/ethnicity and by tumor subtype is ongoing, and likely to lead to model improvement [305][306][307][308][309][310][311][312][313][314][315][316].…”
Section: Risk Prediction Modelsmentioning
confidence: 99%